Ageing and Fiscal Imbalances Across Generations: Concepts of Measurement - Robert Fenge; Martin Werding (Center for Economic Studies and ifo Institute (CESifo), 2003)
In the literature, several approaches have been taken to measure the impact of demographic ageing on public pension schemes, with particular attention being paid to potential fiscal imbalances across the generations involved in demographic transition. In this paper, we review three of these measures - viz., net pension liabilities and general government fiscal balances as suggested by the OECD, as well as generational accounting in the Auerbach- Kotlikoff tradition. We show how these approaches are related to each other by the general idea that unfunded pensions create an implicit public debt, and we discuss the problems involved in applying and interpreting them in a real-world context. In addition, we suggest the implicit tax entailed in public pensions as a further concept for measuring the inter-generational distribution of burdens arising in ageing populations. The notion of an implicit tax is straightforward from simple pension algebra; it is easy to interpret in a theoretical perspective; and it can be introduced to various kinds of applied work using micro-level data.
Keywords: 330; demographic ageing; public pensions; fiscal policy; inter-generational redistribution; measurement